Macrostructures vs microstructures in evaporite detachments: An example from the Salt Range, Pakistan. (1st December 2015) - Richards, L.; King, R.C.; Collins, A.S.; Sayab, M.; Khan, M.A.; Haneef, M.; Morley, C.K.; Warren, J.
Highlights: Structural measurements mirror the larger scale deformation in the region. Rheological heterogeneity in the detachment indicates a varied response to stress. Limited meso-/micro-structure correlation due to telogenetic alteration. Current salt deformation understanding does not reflect true complexity. Abstract: The Salt Range, Pakistan is the surface expression of an evaporite detachment over which the Potwar Plateau fold-thrust belt has moved. Whilst previous publications regarding this region have focused on the petroleum prospectivity, deformation, and large-scale processes, this paper characterises the Salt Range detachment at the meso-(10 cm to 10s of metres) and micro-scale (cm to μm) and examines correlations to the macro-scale (10s of metres to kms). Two detailed scaled cross sections are analysed alongside structural measurements to characterise the detachment at the meso-scale with optical analysis of microstructures that formed during deformation characterising the micro-scale. Both ductile and brittle features observed in cross section indicate composite deformation processes acting simultaneously; this contrasts with models of salt detachments behaving homogeneously. Microstructural analysis indicates processes of grain boundary migration and crystal lattice distortions. The microstructurally revealed competition between intra-crystalline deformation and recrystallization at shallow depths and low temperatures links passes up-scale to mesoscale evaporite mylonites and progressively in the weaker units, whereas more brittle processes operate in the stronger lithologies in this near-unique outcrop of a the emergent toe of a major salt-bearing detachment fault.